Liquid-phase alkylation of phenol with long-chain olefins over WOx/ZrO2 solid acid catalysts - Sarish, S.; Devassy, Biju M.; Bohringer, Walter; Fletcher, Jack C. Q.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2005)
The liquid-phase alkylation of phenol with 1-dodecene was carried out over WOx/ZrO2 solid acid catalysts. The catalysts were prepared by wet impregnation method using zirconium oxyhydroxide and ammonium metatungstate. Catalysts with different WO3 loading (5-30 wt.%) were prepared and calcined at 800 degrees C and catalyst with 15% WO3 was calcined from 700-850 degrees C. All the catalysts were characterized by surface area, XRD, and FTIR. The catalyst with 15% WO3 calcined at 800 degrees C (15 WZ-800) was found to be the most active in the reaction. The effect of temperature, molar ratio and catalyst weight on dodecene conversion and products selectivity was studied in detail. Under the optimized reaction conditions of 120 degrees C, phenol/1-dodecene molar ratio 2 and time 2 h, the catalyst 15 WZ-800 gave > 99% dodecene conversion with 90% dodecylphenol selectivity. Comparison of the catalytic activity of 15 WZ-800 with sulfated zirconia calcined at 500 degrees C (SZ-500) and HP zeolite showed that activity of SZ-500 was lower than that of 15 WZ-800, while HP zeolite showed negligible activity. It is observed that the presence of water in the reaction mixture was detrimental to the catalytic activity of WOx/ZrO2. The catalyst 15 WZ-800 also found to be an efficient catalyst for alkylation of phenol with long-chain olefins like 1-octene and 1-decene. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Alkylation; long-chain olefins; phenol; tungsten oxide; Zirconia

Silicotungstate-modified zirconia as an efficient catalyst for phenol tert-butylation - Devassy, Biju M.; Shanbhag, G. V.; Mirajkar, Subhash P.; Bohringer, Walter; Fletcher, Jack C. Q.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2005)
The alkylation of phenol with tert-butanol was investigated using zirconia modified with silicotungstic acid (STA) as catalysts. The catalysts with different STA loading (5-25 wt.% calcined at 750 degrees C) and calcination temperature (15 wt.% calcined from 350 to 850 degrees C) were prepared and characterized by X-ray diffraction and NH3-TPD measurements. The XRD results indicate that STA stabilizes the tetragonal phase of zirconia. The catalyst with 15% STA on ZrO2 calcined at 750 degrees C shows the highest acidity and hence highest activity. Under the reaction conditions of 140 degrees C, tert-butanol/phenol molar ratio of 2 and LHSV of 4 h(-1), phenol conversion was 95.4% with selectivity to 2-tert-butyl phenol 4.3%, 4-tert-butyl phenol 59.2% and 2,4-di-tert-butyl phenol 35.8%. The reaction was studied as a function of time for 50 It without appreciable change in phenol conversion and product selectivity. The deactivated catalyst could be regenerated by calcination with out appreciable lose in catalytic activity and product selectivity. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: phenol; Silicotungstic acid; tert-butylation; Zirconia

Synthesis of linear alkyl benzenes over zirconia-supported 12-molybdophosphoric acid catalysts - Devassy, Biju M.; Lefebvre, F.; Bohringer, Walter; Fletcher, Jack C. Q.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A - Chemical, 2005)
The liquid-phase alkylation of benzene with 1-octene and 1-dodecene was investigated using zirconia-supported 12-molybdophosphoric acid (MPA) as catalyst. The catalysts with different MPA loading (5-25 wt.% calcined at 700 degrees C) and calcination temperature (15 wt.% calcined from 500 to 750 degrees C) were prepared by suspending zirconium oxyhydroxide in methanol solution of MPA followed by drying and calcination. These catalysts were characterized by X-ray diffraction, and P-31 MAS NMR spectroscopy measurements. The XRD results indicated that MPA stabilizes the tetragonal phase of zirconia. 3 1 P MAS NMR spectra show that the nature of phosphorous species depend on MPA loading and calcination temperature, and it show the existence of three types of phosphorous species, one is the Keggin unit and the other is the decomposition product of MPA and third one an unidentified species. FTIR pyridine adsorption on 15% MPA catalyst calcined at 700 degrees C showed the presence both Bronsted and Lewis acidity. Under the reaction conditions of 83 C, benzene/1-olefin molar ratio of 10 (time, 1 h), the most active catalyst, 15% MPA calcined at 700 C gave more than 90% olefin conversion with selectivity to 2-phenyl octane, 55% and 2-phenyl dodecane, 45%. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: 12-molybdophosphoric acid; benzene alkylation; linear alkyl benzene; Zirconia

Zirconia-supported phosphotungstic acid as catalyst for alkylation of phenol with benzyl alcohol - Devassy, Biju M.; Shanbhag, G. V.; Lefebvre, F.; Bohringer, Walter; Fletcher, Jack C. Q.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A - Chemical, 2005)
The liquid-phase alkylation of phenol with benzyl alcohol was carried out using zirconia-supported phosphotungstic acid (PTA) as catalyst. The catalysts with different PTA loadings (5-20 wt.% calcined at 750 degrees C) and calcination temperature (15 wt.% calcined from 650 to 850 degrees C) were prepared and characterized by (31)p MAS NMR and FT-IR pyridine adsorption spectroscopy. The catalyst with optimum PTA loading (15%) and calcination temperature (750 degrees C) was prepared in different solvents. 31p MAS NMR spectra of the catalysts showed two types of phosphorous species, one is the Keggin unit and the other is the decomposition product of PTA and the relative amount of each depends on PTA loading, calcination temperature and the solvent used for the catalyst preparation. The catalysts with 15% PTA on zirconia calcined at 750 degrees C showed the highest Bronsted acidity. At 130 degrees C and phenol/benzyl alcohol molar ratio of 2 (time, I h), the most active catalyst, 15% PTA calcined at 750 degrees C gave 98% benzyl alcohol conversion with 83% benzyl phenol selectivity. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: Benzylation; phenol; Phosphotungstic acid; Zirconia

Highly efficient and chemo selective catalyst system for the synthesis of blossom orange fragrance and flavoring compounds - Justus, Josena; Vinu, Ajayan; Devassy, Biju M.; Balasubramanian, Veerappan V.; Bohringer, Walter; Fletcher, Jack C. Q.; Halligudi, Shivaraj B. (Catalysis Communications, 2008)
{Acetal and acylal formation reactions of organic compounds are efficiently catalyzed by zirconia-supported mixed oxide systems under liquid-phase reaction conditions. 15WZ-750 (where
Keywords: Acetal; acylal; Silicotungstic acid; tungsten oxide; tungstophosphoric acid; Zirconia

Comparative study on liquid phase alkylation of 2-methylnaphthalene with long chain olefins using different solid acid catalysts - Lucas, Nishita; Bordoloi, Ankur; Amrute, Amol P.; Kasinathan, Palraj; Vinu, Ajayan; Bohringer, Walter; Fletcher, Jack C. Q.; Halligudi, Shivaraj B. (Applied Catalysis A-General, 2009)
A comparative study has been made over a variety of solid acid catalysts, which include isopoly and heteropoly ions supported on various supports such as zirconia, titania, a large variety of zeolites and a couple of mesoporous materials for liquid phasealkylation of 2-methylnaphthalene with 1-octene.All the catalyst systems were characterized by nitrogen sorption analysis, X-ray diffraction and NH(3)-TPD. Inspite of their high acid amounts zeolites gave poor catalytic performance due to their diffusional constraints; on the other hand mesoporous materials lacked diffusional constraints but due to their low acid amounts resulted in poor conversions. lsopoly and heteropoly ions supported on zirconia and titania were found to be catalytically active for the reaction due to total surface acidity. Among them, isopolytungstate supported on zirconia exhibited the best catalytic activity and was used for further optimization of reaction conditions. Excellent conversions of all olefins (>92%) with high selectivity of monoalkylmethylnaphthalene (>95%) was obtained under optimized reaction conditions. The catalyst could be recycled for several times without any obvious loss of its activity. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: 2-Methylnaphthalene; Alkylation; Long chain olefins; Zirconia